Impedimetric Graphene-based Biosensor for the Detection of Escherichia Coli DNA - Nurulasma, Zainudin; Mohd Hairul, Ab. Rahim; M. M., Yusoff; K. F., Chong (Royal Society of Chemistry, 2014)
A label-free impedimetric DNA biosensor based on graphene nanosheets has been developed for the detection of Escherichia coli O157:H7 strain GZ-021210. Probe DNA (pDNA) of E. coli was immobilized onto graphene nanosheets by the surface functionalization of graphene with 1-pyrenebutyric acid (PyBA) followed by carbodiimide linkage. The hybridization of complementary DNA (cDNA) of E. coli with the immobilized pDNA increased the electron transfer resistance of the graphene nanosheets, as observed by electrochemical impedance spectroscopy (EIS). The E. coli DNA biosensor displayed a wide range of linear response (1.0 1010 M to 1.0 1014 M), low detection limit (0.7 1015 M), single-base mismatch selectivity, high robustness and good reproducibility. The current work demonstrates an important advancement in the development of a sensitive biosensor for E. coli detection.